Understanding streamflow variability over drylands in a water-scarce region: a case study in Patagonia - Ricetti, Lorenzo (2025)
Water scarcity represents a major global risk, with paramount importance over drylands. Hence, studying the streamflow variability in dryland watersheds is crucial for proper water management. This work studies the streamflow variability in a dryland Patagonian watershed and its associated tropospheric anomalous circulation features. Streamflow anomalies in the different phases of the annual cycle were interrelated and modulated primarily by winter precipitation anomalies. Low streamflow years were driven by anomalous tropospheric circulation patterns consistent with La Niña and, to a lesser extent, the negative phase of the Indian Ocean Dipole. Conversely, high streamflow years were primarily conducted by wet conditions associated with enhanced mean flow baroclinicity, unlinked to the Southern Annular Mode. These results evidence the complex and non-linear behaviour of the streamflow variability in the study region, as low streamflow was modulated at an inter-annual scale. In contrast, high streamflow was primarily influenced by intraseasonal variability.